Draft Genome Sequence of Elizabethkingia anophelis Strain EM361-97 Isolated from the Blood of a Cancer Patient - Lin, Jiun-Nong (Genome Announc, 2016)
Elizabethkingia anophelis EM361-97 was isolated from the blood of a patient with nasopharyngeal carcinoma and lung cancer. We report the draft genome sequence of EM361-97, which contains a G+C content of 35.7% and 3,611 candidate protein-encoding genes.